2008
DOI: 10.25011/cim.v31i4.4781
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological evaluation of immunohistochemical Ki-67 and endothelial nitric oxide synthase expression in intracranial ependymoma

Abstract: Clin Invest Med 2008; 31 (4): E206-E211. AbstractPurpose: To analyze the association between Ki-67 and eNOS expression with the pathological grades of patients with intracranial ependymomas, and to determine its value in distinguishing the progression of the disease. Methods: A clinicopathological study was undertaken in 82 patients with intracranial ependymomas. Tissue samples, obtained by tumour resection, were divided into three groups: low-grade, mid-grade and high-grade ependymomas. Tissue samples obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…NOS1 strongly correlated with astrocytoma grade and proliferation (115), and NOS3 was strongly correlated with astrocytoma grade and VEGF expression (26). NOS3 expression also correlated with elevated tumor grade for ependymomas (134). Elevated expression of NOS2 was also observed in the majority of oligodendrogliomas (10).…”
Section: Nos Expression In Malignant Glioma Patient Specimensmentioning
confidence: 72%
“…NOS1 strongly correlated with astrocytoma grade and proliferation (115), and NOS3 was strongly correlated with astrocytoma grade and VEGF expression (26). NOS3 expression also correlated with elevated tumor grade for ependymomas (134). Elevated expression of NOS2 was also observed in the majority of oligodendrogliomas (10).…”
Section: Nos Expression In Malignant Glioma Patient Specimensmentioning
confidence: 72%
“…In a previous study, cytoplasmic staining for Ki67 was identified in 15% (24/155) of cryostat‐sectioned snap‐frozen primary melanomas 4 . A cytoplasmic and/or cell membrane pattern of immunoreactivity for Ki67 has also been described in tonsil crypt epithelial cells and fetal epithelial lung cells, and in a number of tumors, including basal cell carcinoma, intracranial ependymoma, hyalinizing trabecular adenoma of the thyroid gland, sclerosing hemangioma of the lung, pleomorphic adenoma of the salivary gland, sarcomatoid pleural mesothelioma, renal oncocytoma and 4.7–26% of invasive breast carcinoma cases 1,2,5–9 . In addition, in vitro cytoplasmic localization of Ki67 has been reported in HeLa cell line cultures 10 …”
mentioning
confidence: 89%